2019
DOI: 10.1002/chem.201902102
|View full text |Cite
|
Sign up to set email alerts
|

Central (S) to Central (M=Ir, Rh) to Planar (Metallocene, M=Fe, Ru) Chirality Transfer Using Sulfoxide‐Substituted Mesoionic Carbene Ligands: Synthesis of Bimetallic Planar Chiral Metallocenes

Abstract: Enantiopure bimetallic systems containing three different elements of chirality, namely a main‐group‐based chiral center (sulfur), a transition‐metal chiral center (rhodium or iridium), and a planar chiral element (ferrocene or ruthenocene), have been prepared by a sequence of diastereoselective reactions. The chirality of the chiral sulfur center attached to C‐5 of a 1,2,3‐triazolylidene mesoionic carbene (MIC) ligand coordinated to a metal (Ir, Rh) was transferred through the formation of bimetallic complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…The analogous iridium MIC complexes are well-established. Iridium complexes are popular and show high performance for redox or photochemical and photophysical applications, similar to the previously discussed ruthenium complexes. , CV-based investigations of iridium­(III) complexes containing MIC donor ligands displayed mainly quasi-reversible or irreversible redox processes. ,, Some of the reported MIC iridium complexes are also active as water oxidation catalysts in a photoelectrode setup or in an electrochemical cell. , …”
Section: Redox Photochemical/photophysical Properties Of Metal Complexesmentioning
confidence: 65%
“…The analogous iridium MIC complexes are well-established. Iridium complexes are popular and show high performance for redox or photochemical and photophysical applications, similar to the previously discussed ruthenium complexes. , CV-based investigations of iridium­(III) complexes containing MIC donor ligands displayed mainly quasi-reversible or irreversible redox processes. ,, Some of the reported MIC iridium complexes are also active as water oxidation catalysts in a photoelectrode setup or in an electrochemical cell. , …”
Section: Redox Photochemical/photophysical Properties Of Metal Complexesmentioning
confidence: 65%
“…The LUMO orbital of 4ec À is still localized across the [FeFe] fragment while radical anion 4gc À has the LUMO located in the organic moiety, which is easily reducible (still with strong anodic displacements, giving lower reduction potentials than their saturated congeners, due to the presence of the metals). 23 This proposal nicely explain the "strong effect of the dithiolene and (in their case) tetrachloro-biphenyl dithiolate groups on the level of the LUMO" reported by Gloaguen and Schollhammer. 22 The electrochemical behavior in acidic media of complexes 4e and 4g (as representative examples of complexes having either a saturated or double bond in the bridge joining the sulfur atoms) was next studied.…”
Section: Mechanistic Studiesmentioning
confidence: 53%
“…During our work in the synthesis of transition metal complexes having 1,2,3-triazolylidene (MIC) ligands with enantiopure sulfoxide and sulfoxiimine moieties, [8] we have reported the role of the chiral mesoionic carbene ligand (MIC) in defining the catalytic reactivity of their Au(I) derivatives, [9] preparing enantiopure chiral-at-metal complexes, [10] and enantiopure complexes having chiral-at-metal and chiral planar metallocene moieties. [11] On the other hand, our work in push-pull systems containing a Cr(0) and W(0) Fischer metal carbene moiety, I, clearly demonstrated that the system geometry is reflected in the deactivation of the fluorescence. [12] Analogously, complexes BODIPY-metal carbene II, having remote π-conjugation, allowed to determine the influence of electronic factors in the emission properties of the BODIPY moiety.…”
Section: Introductionmentioning
confidence: 80%